2017
DOI: 10.1055/s-0037-1604394
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Arthroscopic Debridement of the Triangular Fibrocartilage Complex in Adolescents

Abstract: To the best of our knowledge, we are not aware of any reports focusing on results of arthroscopic debridement of triangular fibrocartilage complex (TFCC) tears in immature patients. The purpose of this study was to evaluate our results after arthroscopic debridement of TFCC tears in adolescents. We retrospectively identified all patients of 18 years or less, who received an arthroscopic TFCC debridement due to a traumatic or degenerative tear according to Palmer. These cases were clinically re-evaluated after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…If the patients were not contactable or refused to participate in the study, the last clinical follow-up was used [ 23 , 24 , 25 ]. Three studies had at least one prospective clinical follow-up [ 26 , 27 , 28 ]. The overall study quality was very low with MINORS criteria ranging from 10 to 13 and the Modified Coleman Score (MCS) ranging from 34 to 56.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…If the patients were not contactable or refused to participate in the study, the last clinical follow-up was used [ 23 , 24 , 25 ]. Three studies had at least one prospective clinical follow-up [ 26 , 27 , 28 ]. The overall study quality was very low with MINORS criteria ranging from 10 to 13 and the Modified Coleman Score (MCS) ranging from 34 to 56.…”
Section: Resultsmentioning
confidence: 99%
“…The overall study quality was very low with MINORS criteria ranging from 10 to 13 and the Modified Coleman Score (MCS) ranging from 34 to 56. Six papers reported solely on pediatric and adolescent cases [ 23 , 24 , 25 , 27 , 28 , 29 ], whereas two studies also reported adult cases [ 26 , 30 ]. Terry and Waters [ 29 ] and Wu et al [ 25 ] reported both open and arthroscopic cases, with data of the former being fully extractable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations